2006
DOI: 10.1128/aem.00424-06
|View full text |Cite
|
Sign up to set email alerts
|

Purine Biosynthesis, Riboflavin Production, and Trophic-Phase Span Are Controlled by a Myb-Related Transcription Factor in the Fungus Ashbya gossypii

Abstract: Ashbya gossypii is a natural riboflavin overproducer used in the industrial production of the vitamin. We have isolated an insertional mutant exhibiting higher levels of riboflavin production than the wild type. DNA analysis of the targeted locus in the mutant strain revealed that a syntenic homolog of the Saccharomyces cerevisiae BAS1 gene, a member of the Myb family of transcription factors, was inactivated. Directed gene disruption of AgBAS1 confirmed the phenotype observed for the insertional mutant, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 44 publications
3
68
0
Order By: Relevance
“…A. gossypii has been considered a paradigm of sustainable white biotechnology through its use in the industrial overproduction of riboflavin and other vitamins (16). Indeed, we have previously described metabolically engineered strains of A. gossypii that are able to produce 10-fold more riboflavin than a wild-type (WT) strain (17)(18)(19), and similar results have been achieved for the production of folic acid (J. L. Revuelta, unpublished results). The fermentation processes using A. gossypii have several advantages, such as the mycelial autolysis that occurs in late stationary phase, which avoids costly recovery steps, and its ability to grow in different oil sources and oil-containing wastes (16,20).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…A. gossypii has been considered a paradigm of sustainable white biotechnology through its use in the industrial overproduction of riboflavin and other vitamins (16). Indeed, we have previously described metabolically engineered strains of A. gossypii that are able to produce 10-fold more riboflavin than a wild-type (WT) strain (17)(18)(19), and similar results have been achieved for the production of folic acid (J. L. Revuelta, unpublished results). The fermentation processes using A. gossypii have several advantages, such as the mycelial autolysis that occurs in late stationary phase, which avoids costly recovery steps, and its ability to grow in different oil sources and oil-containing wastes (16,20).…”
supporting
confidence: 55%
“…A. gossypii is considered to be a model organism for the biotechnological production of vitamins, nucleotides, and proteins (19,29,30). Furthermore, it has been reported that A. gossypii is able to accumulate a significant amount of lipid bodies in its multinucleated hyphae (21) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In E. ashbyii the shift from growth to the production phase was accompanied by derepression of GTP cyclohydrolase II and FAD synthetase, whereas the activity of RF synthase was only slightly changed (239). In A. gossypii, the RF production phase was characterized by a strong increase in transcription of several RF biosynthesis genes (RIB3, RIB4, and RIB5 but not RIB2 and RIB7), as well as many other genes involved in transcription, translation, membrane transport, cell architecture, and metabolism (209,292,396,397). The mechanisms involved in the shift from growth to production phase and in the induction of RF synthesis and the nature of the messenger(s) that induces RF oversynthesis remain unknown.…”
Section: Transcriptional Regulation In Mycelial Fungimentioning
confidence: 99%
“…A protocol for insertion mutagenesis of A. gossypii has been developed (391), and a disruption mutant defective in gene BAS1 (encoding a member of the Myb family of transcription factors) has been tagged. Corresponding disruption and knockout strains overexpressed RF (292). BAS1 proved to be involved in adeninemediated repression of the de novo biosynthesis of purine nucleotides.…”
Section: A Gossypiimentioning
confidence: 99%
See 1 more Smart Citation